Climatological Variations in the Intensity of Tropical Cyclones Formed over the North Atlantic Basin Using the Hurricane Maximum Potential Intensity (HuMPI) Model - Albenis Pérez-Alarcón; José C. Fernández-Alvarez (ECAS 2022, 2022)
In this study, we investigated the variations in the intensity of the tropical cyclones (TCs) formed in the North Atlantic basin from 1982 to 2021, based on the outputs from the Hurricane Maximum Potential Intensity (HuMPI) model. To feed HuMPI, we computed the annual Sea Surface Temperature (SST) as the SST average from 1 June to 30 November using the Daily Optimum Interpolation SST database. The information for all major hurricanes (MHs, category 3+ on the Saffir–Simpson wind scale) was obtained from the HURDAT2 dataset. While the trend (p < 0.05) in the mean maximum potential intensity (MPI) was approximately 1.14 m/s per decade for the maximum sustained wind speed and −1.57 hPa/decade for the minimum central pressure, the MH intensity did not exhibit any statistically significant trend. The behaviour of the MPI could be explained by the increase (p < 0.05) of the SST at a rate of 0.20 °C/decade. In addition, the increase of the TC intensity in the last 20 seasons (2002–2021) in relation to the period 1982–2001 was quite similar for MHs and MPI, being an increase of 3.89% and 3.20% for the mean maximum wind speed, respectively. Meanwhile, the minimum central pressure decreased by approximately 0.36% in both cases. This latter result is promising for investigating the changes in TC intensity resulting from global warming based on the HuMPI model.